(untitled) (SAARC Journal of Agriculture, 2023)
Healthy seedling is the best component of the transplant rice, which depends on its growing environment and appropriate nursery management techniques. To assess the effectiveness of various seeding densities and nutrient management in nurseries on seedling growth and yield of Boro rice, an experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, from November 2019 to May 2020. The experiment comprised two factors, viz., seeding density (3): low density (80 g m-2), medium density (100 g m-2), high density (120 g m-2); and nursery nutrient management (6): no nutrient applied, 10 g N m-2, 15 g P m-2, 15 g K m-2 , 10 g N m-2 + 15 g P m-2 + 15 g K m-2, compost 2 kg m-2. The experiment was replicated 3 times following randomized complete block design. With 80 g m-2 seed rate, the highest seedling dry weight, effective tillers hill-1, grains panicle-1 and grain yield were all achieved. Regarding nutrient management, seedlings fertilized with N+P+K produced the highest shoot length, seedling dry weight, effective tillers hill-1, grains panicle-1 and grain yield. In case of interaction, the highest number of effective tillers hill-1 was obtained from 80 g m-2 seeding density with N+P+K application, which eventually resulted in the highest grain yield. Therefore, low seeding density of 80 g m-2 and application of 10 g N m-2 + 15 g P m-2 + 15 g K m-2 in nursery may be practiced for better seedling growth and higher yield of Boro rice. SAARC J. Agric., 21(1): 153-166 (2023)